2020
DOI: 10.1159/000507981
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Acquired Hemolytic Anemia and Pancytopenia Secondary to Pernicious Anemia

Abstract: The commonest etiologies of new-onset pancytopenia are congenital bone marrow failure syndromes, marrow space-occupying lesions, infections, and peripheral destruction. Nutritional deficiencies, including folate and vitamin B12, can occasionally cause pancytopenia. We report a 48-year-old gentleman who presented with a 1-week history of dizziness and upper gastrointestinal bleeding. Laboratory evaluation revealed pancytopenia, macrocytosis, toxic neutrophils, hemolysis, suppressed reticulocyte count, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Hematologic consequences include macrocytosis, hypersegmented neutrophils, leukopenia, thrombocytopenia, and rarely, pancytopenia; in fact, pancytopenia, in which all blood cell lines are decreased, is seen in only 5% of patients with a known B12 deficiency [ 9 ]. Typically, with profound anemia as exhibited in this patient, tachycardia would be an expected associated vital sign, but in this case was normal, likely due to the chronicity of his disease state.…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic consequences include macrocytosis, hypersegmented neutrophils, leukopenia, thrombocytopenia, and rarely, pancytopenia; in fact, pancytopenia, in which all blood cell lines are decreased, is seen in only 5% of patients with a known B12 deficiency [ 9 ]. Typically, with profound anemia as exhibited in this patient, tachycardia would be an expected associated vital sign, but in this case was normal, likely due to the chronicity of his disease state.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 7 ] Megaloblastic anemia in addition to severe B12 deficiency in some cases causes pancytopenia and hemolysis. [ 10 ] The incidence of aplastic anemia varies from 10% to 52.7% of all pancytopenia patients in different studies from all over the world. [ 11 12 ] It was found that the incidence of bleeding manifestation in patients of aplastic anemia having platelet count less than 20,000/cu mm was statistically significant than the patient with platelet count more than 20,000/cu mm (P- value < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Even if a delay could not impair the diagnostic assurance with neurologic symptoms, their treatment would be started promptly to avoid the risk of irreversibility including extensive sensory defects, gait disturbances, and mental changes. The presence of dizziness and generalized weakness for three days, presence of fever, scleral icterus, conjunctival pallor, and hyperpigmentation of the knuckles of both hands presented in a 48-year-old male case reported by Sasi and Yassin [ 29 ]. On admission, the patient’s values were: Hb 6.5 g/dL, MCV 102.6 fL.…”
Section: Vitamin B 12 and Anemiamentioning
confidence: 99%
“…Hussain et al[28].Full blood profile, Vitamin B 12 , Folate, Haptoglobin, MMA, Intrinsic factor antibody At six-month follow-up clinical and laboratory analysis improvement (e.g., hemoglobin improved to 11.9 gm/d).Sasi and Yassin[29].Full blood profile, B 12 level, Bilirubin, LDH Haptoglobin, direct antiglobulin (DAT) Serum iron, thyroid functions Blood cell counts started showing an upward trend on day 4 after starting the treatment. On discharge, after 10 days of hospital stay, improvement of blood profile and vitamin B 12 (from values <37 pmol/L to 369 pmol/L), remission of all symptoms.…”
mentioning
confidence: 98%